Pengaruh Current Ratio, Debt to Equity Ratio, Dan Return on Assets terhadap Kebijakan Deviden pada Perusahaan Property dan Real Estate yang Terdaftar di Bursa Efek Indonesia - Enda Noviyanti Simorangkir; Teguh Hakim Prajoggi; Enzelina Enzelina; Edo Hasugian; Desy Desy (COSTING : Journal of Economic, Business and Accounting, 2020)
In investing capital an investor needs a company's financial statements that will help in making investment decisions. This study aims to analyze and test the effect of the current ratio, debt to equity ratio, return on assets on dividend payout ratios in property and real estate companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2017 period. The research method in this study uses a quantitative approach. There were 46 companies that were used as populations in this study and by using a purposive sampling technique 13 samples were also obtained. The data analysis testing method used is multiple linear regression analysis using the classic assumption test. The results of this study show that the current ratio, debt to equity ratio, and return on assets have a simultaneous effect on dividend policy on property and real estate companies listed on the IDX for the 2015-2017 period with a Fcount value of 4.309> Ftable of 2, 87. Partially the debt to equity ratio, return on assets has no effect on dividend policy while the current ratio partially has a positive effect on dividend policy. The results of the analysis of the coefficient of determination show the Adjusted R2 value of 0.207, meaning that the variation in the variable dividend payout ratio can be explained by variations in the current ratio variable, debt to equity ratio and return on assets by 20.7% while the remaining 70.3%, is described by other variables outside research. Keywords: Current Ratio (CR), Debt to Equity Ratio (DER), Return on Assets (ROA) and dividend policy